Optimizing Soil Drainage Strategies for Waterlogging Mitigation in Vertisol: Temporal Interventions for Lentil Production in Eastern Amhara Highlands, Ethiopia - Taye, Tilahun; Lebay, Muluken; Mohammed, Awol (Department of Agronomy and Horticulture, IPB University, 2025)
In Ethiopia’s central highlands, lentils are the second most important pulse crop, but their productivity is constrained by waterlogging and a lack of clear recommendations on optimal planting times. This study aimed to evaluate the effectiveness of various soil drainage techniques for lentil sowing, determine the optimal planting time for vertisols, and develop environmentally sustainable management strategies for lentil cultivation. Field experiments were conducted during the 2022 and 2023 cropping seasons in the eastern Ethiopian highlands, specifically in the Legehida and Wereilu districts of the Amhara region. The study tested three planting times (July, August, and September) and two land management practices (sowing with drainage on raised beds and sowing on flat beds) arranged in a factorial randomized complete block design (RCBD). The results showed highly significant differences in both locations. In Legehida, early planting on raised beds increased yield by 1004.78% and biomass by 642.13% compared to late planting. Yields were 1184.67% higher with raised beds than with flat beds or traditional farmer practices, which also showed a 541.86% increase in biomass. Similarly, in Wereilu, early planting on raised beds resulted in a highly significant improvement (p ≤ 0.05) over farmer practices. Therefore, in vertisol areas prone to waterlogging, early sowing of lentils on 120 cm wide raised beds after drainage is an effective strategy to enhance yield and biomass production.